Inhomogeneous Deformation of Interstitial Free Steel during the High Pressure Torsion Process - Yuepeng Song; Miaomiao chen; Wenke Wang; Baoyan Xu; Dongsheng Gao; Shuai Zhang; 김형섭 (Korean Journal of Metals and Materials, 2017)
Interstitial free (IF) steel disks were subjected to various degrees of revolution during application of the high-pressure torsion (HPT) process, and the resulting distributions of hardness and microstructure during the early torsion stage of high-pressure torsion (HPT) were investigated using experimental and simulation approaches. The results indicated that the deformation in the HPT-processed IF steel disk was inhomogeneous, producing low hardness in the center and high hardness in the edge region. The experimental results, including the hardness and microstructure distributions, indicated that the severe deformation zone proceeds gradually from the center to the edge of the HPT disks in the early torsion stage, and also confirmed verify that the deformation on the upper surface of the disks lags behind that on the bottom surface. Simulation results from a finite element method analysis strongly supported the experimental conclusions. KCI Citation Count: 3